Citizens’ media in latin america - Rodríguez, Clemencia (2019)
There are several reasons that explain why community and citizens’ media are so widespread and popular in Latin America. This chapter offers a series of short vignettes set in Colombia that describe the intricate processes that developed there since the 1920s and simultaneously elsewhere across Latin America, spreading the notion that agency and participation are everyone’s right. These vignettes highlight why understanding community and citizens’ media in Latin America requires recognizing the long history of radical politics in the region and the wide dissemination of leftist ideologies that popularized notions of popular participation and political agency as rights. The chapter also brings into dialogue the work of Peruvian scholar Rosa María Alfaro, who was instrumental in transforming communication scholarship in Latin America and is an early example of citizens’ media in Latin America. Including a translation of this key early text by Alfaro was a challenge, because the field is vast and there is so much material that has never been translated into English or published outside of Latin America. In selecting the following piece, the intention is to maintain the centrality of both theory and practice and to show how citizens’ media in Latin America cannot be understood unless we take into consideration what social movements and grassroots communities did in the region and how Latin American scholars thought about the region.